PENGARUH PROGRAM “LAPOR PAK!” TRANS7 TERHADAP MINAT MENONTON : (SURVEI PADA MAHASISWA ILMU KOMUNIKASI UMJ ANGAKATAN 2022) - Safitri, Ridha; Habibi, Mulkan (Triwikrama: Jurnal Ilmu Sosial, 2025)
Abstract The Lapor Pak Program is a crime comedy show that airs on Trans7 with the concept of variety comedy, by comedicizing criminal cases, current issues, and artist gossip. Television comedy program Lapor pak! Being one of the best performing television programs and one of the most influential television programs in Indonesia is evidenced by Lapor pak! In 2023, has awarded the Primetime Non-Drama Most Popular Program at the 2021 Indonesia Television Awards. The purpose of this study was to measure the Lapor Pak Program in Trans7 against UMJ 2022 communication science students, measure the Interest in Watching UMJ 2022 communication science students, and measure the effect of the Lapor Pak Program on Interest in Watching UMJ 2022 communication science students. This study used the Event Program theory (Format Power, Star Power, Information Power) and the Watch Interest Theory (Cognitive, Affective, Conative). The research method used in this study is quantitative with survey research. Data collection techniques used questionnaires to 116 respondents. The result of this study is that the Lapor Pak Program in Trans7 has a value of 0.704 or 70.4%, which means that the Lapor Pak Program in Trans7 has a value of 70.4% of the program's remaining programs are influenced by other factors. Keywords: Program, Watch Interest, Broadcasting.